2015
DOI: 10.3233/cbm-150473
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating CD14(+)HLA-DR-/low myeloid-derived suppressor cells are associated with poor prognosis in patients with small-cell lung cancer

Abstract: The frequency of CD14(+)HLA-DR-/low MDSCs could be considered as a poor prognostic predictor in SCLC and the elimination of MDSCs during medical interventions may improve the prognosis of SCLC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Immature myeloid cells, including MDSCs and TAMs, are essential components of the tumour stroma which are deeply intertwined in the course of tumour development and tumour recurrence and have emerged as key immune modulators that suppress antitumour immune responses through a variety of mechanisms . Clinical studies have also demonstrated that MDSCs are critical tumour‐promoting immune cells correlating with poor clinical outcome, including tumour metastasis and survival . Our previous study revealed that the accumulation of MDSCs and TAMs significantly associated with activation of immune checkpoint molecule PD‐1 , CTLA‐4 and B7‐H4 .…”
Section: Discussionmentioning
confidence: 94%
“…Immature myeloid cells, including MDSCs and TAMs, are essential components of the tumour stroma which are deeply intertwined in the course of tumour development and tumour recurrence and have emerged as key immune modulators that suppress antitumour immune responses through a variety of mechanisms . Clinical studies have also demonstrated that MDSCs are critical tumour‐promoting immune cells correlating with poor clinical outcome, including tumour metastasis and survival . Our previous study revealed that the accumulation of MDSCs and TAMs significantly associated with activation of immune checkpoint molecule PD‐1 , CTLA‐4 and B7‐H4 .…”
Section: Discussionmentioning
confidence: 94%
“…MDSCs are a heterogeneous population of cells with a marked ability to suppress T cell responses 24 and are considered an indicator of poor prognosis in some cancers. 25,26 Tregs are a subpopulation of suppressor T cells that generally suppress or downregulate the induction and proliferation of effector T cells. 27 OVs can effectively The heatmap shows the expression of immune signatures containing 681 immune-related genes in bilateral tumors.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still no uniform standards for surface molecular markers of human MDSCs, and many other markers are being reported gradually. From the perspective of LC, according to multicolor immunofluorescence staining evaluated by fluorescenceactivated cell sorting (FACS), the following phenotypes of MDSCs have been reported (shown in Table 1): CD11b + CD14 − CD15 + CD33 + [14], CD11b + CD14 + S100A9 + [15], CD16 low CD11b + CD14 − HLA-DR − CD15 + CD33 + [16], CD14 + HLA-DR −/low [17,18], B7-H3 + CD14 + HLA-DR −/low [19], CD11b + CD14 − HLA-DR − CD33 + CD15 + ILT3 high [20], Lin − CD14 − CD11b + CD39 + CD73 + [21], Lin − CD14 + CD11b + C D39 + CD73 + [21], Lin − CD14 + CD15 + H LA-DR − [22], Lin − C D14 + CD15 − HLA-DR − [22], Lin − CD14 − HLA-DR − [22], Lin-CD33 + CD14 + CD15 − HLA-DR − [25], CD33 + CD11b + CD14 − [27], CD33 + CD11b + CD14 + HLA-DR −/low [27], and CCR 5 + HLA-DR −/low CD11b + CD14 + CD15 − [28].…”
Section: Main Phenotypic and Functional Characteristics Of Mdscsmentioning
confidence: 99%
“…These suppressive cells upregulated the expression of gp91 phox , an important component of the ROS-generating enzyme NADPH oxidase [17]. Subsequently, for small cell lung cancer (SCLC) patients, the frequency of CD14 + HLA-DR −/low MDSCs was also found to be negatively correlated with clinical outcomes [18]. Zhang et al identified a new subset of MDSCs in the tumor microenvironment of NSCLC, B7-H3 + CD14 + HLA-DR −/low MDSCs (B7-H3 + MDSCs).…”
Section: Role Of Mdscs In the Development Of Lcmentioning
confidence: 99%